Biosensors based on carbon paste electrodes using immobilized dehydrogenase enzymes. An overview and trends - Lobo-Castañón, Maria Jesus; Alvarez-Crespo, Suzana L.; Alvarez-Gonzalez, Maria Isabel; Saidman, Silvana B.; Miranda-Ordieres, Arturo José; Tunon-Blanco, Paulino (Univerzita Pardubice, 1997)
Amperometric biosensors based on two different NADH catalytic systems are presented. Common to both types is the design strategy which consists in the direct mixing of the NAD' -dependent dehydrogenase enzymes and other modifying molecules with the carbon paste combined with physical barriers like dialysis membranes or conducting polymers. One type is based on the use of a redox mediator (the phenothiazine dye Toluidine Blue O) to make possible the electrocatalytic oxidation of the enzymatically produced NADH at potentials close to 0 V. The second type is based on the use of the electrochemically generated conducting polymers poly(o-aminophenol) (PAP) and poly(ophenylenediamine) (PPD), which allow not only the immobilization of enzyme and cofactor at the electrode surface but also the amperometric detection of NADH at potentials as low as 0 V without other immobilized electron transfer mediators. An ethanol biosensor based on the first catalytic system and ethanol, lactate and glutamate sensors based on the second one are presented.